2009
DOI: 10.3989/scimar.2009.73s1059
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different salinity conditions on egg buoyancy and development and yolk sac larval survival and morphometric traits of Baltic Sea sprat (<i>Sprattus sprattus balticus</i> Schneider)

Abstract: SUMARY:The small pelagic sprat (Sprattus sprattus) is a key ecologic player in the Baltic Sea. However, there is longterm variability in recruitment which is thought to be influenced by fluctuations in abiotic and biotic conditions experienced during the early life stages. This study concentrates on the influence of different ambient salinities on sprat egg development, egg buoyancy and survival as well as early yolk sac larval morphometric traits. Egg buoyancy significantly decreased with increasing salinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…For example, trait structure and redundancy are intrinsically correlated with environmental conditions, and we found that sensitivity was also related to environmental change in both ecosystems. In the EEC, salinity changes may have contributed to declines in species with small pelagic eggs and larvae, as salinity influences egg buoyancy and survival (Nissling, Nyberg, & Petereit, ; Petereit et al, ; Sundby & Kristiansen, ). However, salinity changes in the EEC were much lower than those normally reported to impact fish community structure (Petereit et al, ; Sirot et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, trait structure and redundancy are intrinsically correlated with environmental conditions, and we found that sensitivity was also related to environmental change in both ecosystems. In the EEC, salinity changes may have contributed to declines in species with small pelagic eggs and larvae, as salinity influences egg buoyancy and survival (Nissling, Nyberg, & Petereit, ; Petereit et al, ; Sundby & Kristiansen, ). However, salinity changes in the EEC were much lower than those normally reported to impact fish community structure (Petereit et al, ; Sirot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…SST is a primary driver of species’ distributions and abundances globally, and SST warming can profoundly impact marine fish communities, which are highly responsive to changes in temperature (Simpson et al, ). Salinity can influence community structure through physiological responses, impacts on larval success, and shifts between stenohaline and euryhaline species (Petereit et al, ; Sirot et al, ). Although chlorophyll‐ a can also determine community structure through bottom‐up control and through larval success and recruitment (Beaugrand, ; Capuzzo et al, ), spatially resolved data for chlorophyll‐ a were not available prior to 1998.…”
Section: Methodsmentioning
confidence: 99%
“…It has to be noted that a synchronous warming of all water layers as simulated in this study is probably not a realistic scenario. It is more likely that changes in water circulation and vertical mixing will profoundly affect stratification dynamics and oxygen supply to the deep basins, which may also affect survival and growth of sprat early life stages (Petereit et al 2009;Voss et al 2011). Besides warming, a number of other physical processes will be impacted by climate changes that have been correlated with sprat survival.…”
Section: Discussionmentioning
confidence: 99%
“…A future warming scenario, as predicted by the IPCC (2007), is likely to affect all depth strata in the Baltic, and hence all life stages of sprat, since the turnover rate of the entire water body in the deep basins of the Baltic is comparatively high (Meier 2005). In addition, increased precipitation within the Baltic watershed in combination with less frequent inflow events of more saline North Sea water is predicted to lower salinities (Meier 2006), which will in turn affect the vertical distribution of and hence ambient temperature experienced by sprat early life stages (Petereit et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…After a settling time of 60 min, the position of every single egg in the salinity gradient column was recorded to calculate the respective density value. This general method has been regularly applied to measure fish egg density (neutral egg buoyancy) for various Baltic fish species including cod, sprat and flatfish from other areas of the Baltic Sea (Nissling et al, 1994(Nissling et al, , 2002Petereit et al, 2009). We used density gradient columns similar to the setup described by Coombs (1981) and Coombs et al (1985).…”
Section: Gametes Acquisition and Processingmentioning
confidence: 99%